The Line is Death: Animal Fugitivity and Urban Planning: Review of Maan Barua, Lively Cities: Reconfiguring Urban Ecology and Peter S. Alagona, The Accidental Ecosystem: People in Wildlife in American Cities - Grigorovich, Imogen (Humanimalia, 2024)
Reviewed in this essay: Maan Barua, Lively Cities: Reconfiguring Urban Ecology. Minneapolis: University of Minnesota Press, 2023. viii + 373 pp. 53 illus. 30.00 (pb). Peter S. Alagona, The Accidental Ecosystem: People in Wildlife in American Cities. Oakland: University of California Press, 2022. xvi + 276 pp. 10 illus. 26.95 (hb)